Nonaqueous electrolyte power storage element and manufacturing method thereof

By using a fluorinated ether and cyclic carbonate solvent system, the discharge capacity and energy density of non-hydrogen electrolytic elements are enhanced, addressing the limitations of conventional systems through improved contact area and reduced viscosity.

JP2025016261APending Publication Date: 2025-01-31GS YUASA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023119411
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Conventional non-hydrogen electrolyte solutions, particularly those containing sulfur-based active materials and porous carbon, suffer from low discharge capacity per mass due to high viscosity and limited contact area, leading to insufficient energy density in non-hydrogen electrolytic elements.

Method used

Incorporating a non-aqueous solvent system with a fluorinated ether and cyclic carbonate, where the fluorinated ether is represented by R1-O-R2, with R1 being a fluoride alkyl group of 1 or 3 or less carbon atoms and R2 being an alkyl group of 1 or 2 carbon atoms, to enhance the contact area and reduce viscosity, thereby increasing the discharge capacity.

Benefits of technology

The proposed solvent system improves the discharge capacity per mass of sulfur-based active materials by enhancing the contact area and reducing viscosity, resulting in higher energy density in non-hydrogen electrolytic elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016261000001_ABST
    Figure 2025016261000001_ABST
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte power storage element of which the discharge capacity per mass of a sulfur-based active material is increased, and a manufacturing method of such a nonaqueous electrolyte power storage element.SOLUTION: A nonaqueous electrolyte power storage element comprises a positive electrode, which contains a complex of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte containing a nonaqueous solvent. The nonaqueous solvent contains at least one kind of cyclic carbonate, which is selected from between a fluorinated cyclic carbonate and an unsaturated cyclic carbonate, and fluorinated ether. A content of the cyclic carbonate in the nonaqueous solvent exceeds 50 vol%, and the fluorinated ether is expressed by a following formula (1): R1-O-R2 ...(1) (in the formula (1), R1 is a fluorinated alkyl group of which the number of carbon atoms is 1 or more and 3 or less, and R2 is an alkyl group of which the number of carbon atoms is 1 or 2).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element and a method for producing the same. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions such as lithium ions between the two electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] Known nonaqueous electrolyte storage elements include lithium-sulfur batteries (Li-S batteries) and other nonaqueous electrolyte storage elements that use a sulfur-based active material in the positive electrode (see Patent Document 1). Sulfur-based active materials have a large theoretical capacity, and nonaqueous electrolyte storage elements that use a sulfur-based active material in the positive electrode are expected to have high energy density. In addition, since sulfur-based active materials have low electronic conductivity, a composite of a sulfur-based active material and a conductive agent such as porous carbon is sometimes used in the positive electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-95390 A Summary of the Invention [Problem to be solved by the invention]

[0005] In a non-aqueous electrolyte storage element using a sulfur-based active material in the positive electrode, when a non-aqueous electrolyte containing a non-aqueous solvent mainly composed of ether is used, a charge / discharge reaction proceeds due to a shuttle reaction caused by polysulfides formed in the positive electrode dissolving into the non-aqueous electrolyte. In contrast, in a non-aqueous electrolyte storage element using a sulfur-based active material in the positive electrode, when a non-aqueous electrolyte containing a non-aqueous solvent mainly composed of carbonate such as cyclic carbonate is used, a coating is formed on the composite surface of the positive electrode by the reaction between the positive electrode and the non-aqueous electrolyte (cyclic carbonate, etc.) during initial discharge, and then, the charge / discharge reaction proceeds due to the solid-phase diffusion of charge transport ions through this coating. Thus, in a non-aqueous electrolyte storage element using sulfur in the positive electrode, it is considered that the reaction mechanism of the positive electrode occurring during charge / discharge is different between the case where a non-aqueous electrolyte containing a non-aqueous solvent mainly composed of ether is used and the case where a non-aqueous electrolyte containing a non-aqueous solvent mainly composed of carbonate is used.

[0006] According to the findings of the inventors, among non-aqueous electrolyte storage elements having a positive electrode using a composite of a sulfur-based active material and porous carbon, those having a non-aqueous electrolyte using a cyclic carbonate such as fluoroethylene carbonate or vinylene carbonate are promising as storage elements having a high energy density per mass. On the other hand, non-aqueous electrolyte storage elements using such cyclic carbonates are in need of improvement in that the discharge capacity per mass of the sulfur-based active material is not sufficiently large.

[0007] An object of the present invention is to provide a nonaqueous electrolyte storage element including a positive electrode containing a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte containing a cyclic carbonate, the nonaqueous electrolyte storage element having a large discharge capacity per mass of the sulfur-based active material, and a method for manufacturing such a nonaqueous electrolyte storage element. [Means for solving the problem]

[0008] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode including a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte including a nonaqueous solvent, the nonaqueous solvent including at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates, and a fluorinated ether, the content of the cyclic carbonate in the nonaqueous solvent being more than 50% by volume, and the fluorinated ether being represented by the following formula (1): R 1 -OR 2 (1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

[0009] A method for producing a nonaqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode including a composite of a sulfur-based active material and porous carbon, and preparing a nonaqueous electrolyte including a nonaqueous solvent, wherein the nonaqueous solvent includes at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates, and a fluorinated ether, the content of the cyclic carbonate in the nonaqueous solvent being more than 50% by volume, and the fluorinated ether being represented by the following formula (1): R 1 -OR 2 (1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte storage element including a positive electrode containing a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte containing a cyclic carbonate, the nonaqueous electrolyte storage element having a large discharge capacity per mass of the sulfur-based active material, and a method for manufacturing such a nonaqueous electrolyte storage element. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] First, an outline of the nonaqueous electrolyte storage element and the method for producing the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0013] [1] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode including a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte including a nonaqueous solvent, the nonaqueous solvent including at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates, and a fluorinated ether, the content of the cyclic carbonate in the nonaqueous solvent being more than 50% by volume, and the fluorinated ether being represented by the following formula (1): R 1 -OR 2 (1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

[0014] The nonaqueous electrolyte storage element described in [1] above is a nonaqueous electrolyte storage element including a positive electrode containing a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte containing a cyclic carbonate, and has a large discharge capacity per mass of the sulfur-based active material. The reason for this is unclear, but the following reason is presumed. In a conventional nonaqueous electrolyte storage element including a positive electrode containing a composite of a sulfur-based active material and porous carbon (hereinafter also simply referred to as a "composite") and a nonaqueous electrolyte containing a cyclic carbonate, one of the factors that causes the discharge capacity to be insufficiently large is thought to be that the contact area between the composite and the nonaqueous electrolyte is small due to the high viscosity of the nonaqueous electrolyte. The fluorinated ether represented by the above formula (1) has a relatively low molecular weight and a low viscosity. In addition, the fluorinated ether represented by the above formula (1) has an alkyl group and a fluorinated alkyl group, and the alkyl group has a high affinity with the porous carbon of the composite. By including such a fluorinated ether in the nonaqueous electrolyte, the viscosity of the nonaqueous electrolyte is reduced, and the wettability of the nonaqueous electrolyte to the composite is improved. For this reason, it is presumed that in the nonaqueous electrolyte storage element described in [1] above, the contact area between the composite and the nonaqueous electrolyte is large, and the discharge capacity per mass of the sulfur-based active material is large.

[0015] The content of each component constituting the non-aqueous solvent is measured by liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). Specifically, the measurement is performed as follows. The LC-MS and GC-MS measurements are performed consecutively under the same conditions. 1. Collection of non-aqueous electrolyte First, the nonaqueous electrolyte storage element is disassembled to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed, the nonaqueous electrolyte storage element is subjected to centrifugation to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed even after centrifugation, an extraction solvent (e.g., acetonitrile) is injected into the nonaqueous electrolyte storage element, and the nonaqueous electrolyte diluted with the extraction solvent is removed. 2.LC-MS The components of the collected non-aqueous electrolyte are analyzed by LC-MS. The LC-MS analysis is performed in the following order of qualitative analysis and quantitative analysis. The LC-MS analysis is performed using Waters' "Acquity H" and "Xevo G2-5QTof" instruments. Water is used as the eluent. (qualitative analysis) The measurement sample (non-aqueous electrolyte) is subjected to LC-MS analysis. If the peaks in the obtained liquid chromatogram cannot be separated, a GC-MS analysis, described below, is performed instead of the LC-MS analysis. If the peaks can be separated, the components contained in the measurement sample are predicted from the MS spectrum of each peak. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to LC-MS analysis. The retention times and MS spectrum of the peaks corresponding to each predicted component of the measurement sample are compared with the retention times and MS spectrum of the peaks of a known sample of each predicted component, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. First, a known sample of the predicted component with a known concentration is measured by LC-MS, and a calibration curve is created by calculating the peak area. The calibration curve is calculated using the coefficient of determination (r 2 ) is created so that it is between 0.999 and 1. The amount of the predicted component in the measurement sample is calculated from the calibration curve and the area of ​​the peak of the predicted component in the measurement sample. The above process is performed for all peaks detected in the LC-MS analysis of the measurement sample, and the amount of each predicted component is calculated. 3.GC-MS The GC-MS analysis is carried out in the following order: qualitative analysis and quantitative analysis. The GC-MS analysis equipment used is the Agilent 5975C. Argon is used as the carrier gas. (qualitative analysis) A measurement sample (non-aqueous electrolyte) is subjected to GC-MS analysis. The components contained in the sample are predicted from the MS spectrum of each peak in the obtained gas chromatogram. A known sample of the predicted components is subjected to GC-MS analysis. The retention time and MS spectrum of the peak corresponding to each predicted component of the measurement sample are compared with the retention time and MS spectrum of the peak of a known sample of each predicted component, and if they match, the above prediction is presumed to be correct. (Quantitative analysis) The quantitative analysis is performed by the calibration curve method. The quantitative analysis by GC-MS is performed in the same manner as the quantitative analysis by LC-MS described above, and the content of each predicted component is determined. 4. Calculation of the content of each component The total content of each predicted component (i.e., each component) measured by LC-MS or GC-MS is regarded as the content of the non-aqueous solvent, and the content of each component in the non-aqueous solvent is calculated. Note that, when calculating the content (volume %) of each component in the non-aqueous solvent, the mass-based content of each component measured by LC-MS or GC-MS is converted to a volume at 20°C, and the total of the volumetrically converted content of each component is regarded as the content of the non-aqueous solvent. In addition, when an extraction solvent is used, the extraction solvent is excluded from the calculation.

[0016] [2] In the nonaqueous electrolyte storage element according to the above item [1], the content of the fluorinated ether in the nonaqueous solvent may be 10% by volume or more and less than 50% by volume.

[0017] The nonaqueous electrolyte storage element described in the above item [2] has a larger discharge capacity per mass of the sulfur-based active material due to an optimized composition of the nonaqueous solvent, etc.

[0018] [3] The nonaqueous electrolyte storage element according to the above [1] or [2] may further include a negative electrode containing metallic lithium.

[0019] The nonaqueous electrolyte electricity storage element described in [3] above has a negative electrode containing metallic lithium, and thus has further advantages such as a high energy density.

[0020] [4] In the nonaqueous electrolyte storage element according to any one of [1] to [3] above, the fluorinated cyclic carbonate may contain fluoroethylene carbonate.

[0021] [5] In the nonaqueous electrolyte storage element according to any one of [1] to [4] above, the unsaturated cyclic carbonate may contain vinylene carbonate.

[0022] [6] In the nonaqueous electrolyte storage element according to any one of [1] to [5] above, the fluorinated ether may include at least one selected from the group consisting of methyl-1,1,2,2-tetrafluoroethyl ether, ethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,3,3,3-hexafluoropropyl methyl ether, and 1,1,2,3,3,3-hexafluoropropyl ethyl ether.

[0023] [7] In the nonaqueous electrolyte storage element according to any one of [1] to [6] above, the total content of the cyclic carbonate and the fluorinated ether in the nonaqueous solvent may be 80% by volume or more.

[0024] [8] In the nonaqueous electrolyte storage element according to any one of [1] to [7] above, the nonaqueous electrolyte may contain an imide salt.

[0025] [9] In the nonaqueous electrolyte storage element according to any one of [1] to [8] above, the nonaqueous electrolyte may have a viscosity of 0.5 mPa·s or more and 6.5 mPa·s or less at 25° C.

[0026]

[10] A method for producing a nonaqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode including a composite of a sulfur-based active material and porous carbon, and preparing a nonaqueous electrolyte including a nonaqueous solvent, wherein the nonaqueous solvent includes at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates, and a fluorinated ether, the content of the cyclic carbonate in the nonaqueous solvent being more than 50 volume %, and the fluorinated ether being represented by the following formula (1): R 1 -OR 2 (1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

[0027] According to the method for producing a nonaqueous electrolyte storage element described in

[10] above, it is possible to produce a nonaqueous electrolyte storage element including a positive electrode containing a composite of a sulfur-based active material and porous carbon, and a nonaqueous electrolyte containing a cyclic carbonate, the nonaqueous electrolyte storage element having a large discharge capacity per mass of the sulfur-based active material.

[0028] A nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.

[0029] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is impregnated into the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.

[0030] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0031] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0032] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per mass or volume of the positive electrode. The "average thickness" refers to the average value of thicknesses measured at any five points.

[0033] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0034] The positive electrode active material layer includes a composite of a sulfur-based active material and porous carbon. The positive electrode active material layer includes optional components such as a conductive agent, a binder, a dispersant, a thickener, and a filler, as necessary. The positive electrode active material layer is usually formed from a positive electrode mixture including the composite and other optional components.

[0035] In the composite, the sulfur-based active material is usually supported in the pores of the porous carbon. The composite has such a form, so that sufficient electronic conductivity is ensured. The composite may be substantially composed of only the sulfur-based active material and the porous carbon, or may be substantially composed of only the sulfur-based active material and the porous carbon. The composite substantially composed of only the sulfur-based active material and the porous carbon means that the total content of the sulfur-based active material (total of elemental sulfur and sulfur compound) and the porous carbon in the composite is 90% by mass or more, and may be 95% by mass or more, 98% by mass or more, or 99% by mass or more.

[0036] The sulfur-based active material contained in the composite is a component that functions as a positive electrode active material. The sulfur-based active material may be simple sulfur, a sulfur compound, or a mixture of these. That is, the composite may contain sulfur element together with porous carbon. Examples of the sulfur compound include metal sulfides such as lithium sulfide, organic disulfide compounds, and organic sulfur compounds such as carbon sulfide compounds. The sulfur-based active material has the advantages of a large theoretical capacity and low cost.

[0037] The content of the sulfur-based active material in the composite is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 80% by mass. By setting the content of the sulfur-based active material in the composite within the above range, it is possible to increase the discharge capacity per mass of the sulfur-based active material.

[0038] Porous carbon has electrical conductivity. Porous carbon is generally a porous inorganic material whose main constituent element is carbon. The main constituent element refers to the element that is most abundant on a mass basis. The lower limit of the carbon element content in the porous carbon is preferably 70 mass%, more preferably 80 mass%, 90 mass%, 95 mass% or 97 mass%. The upper limit of the carbon element content in the porous carbon may be 100 mass% or 99.9 mass%. The carbon element content in the porous carbon may be within a range that combines any of the above lower limits and the above upper limit. The porous carbon may contain elements other than carbon, such as oxygen and nitrogen.

[0039] The composite can be produced by a conventional method, for example, by heating a mixture of a sulfur-based active material and porous carbon to a temperature equal to or higher than the melting point of the sulfur-based active material, and then cooling the mixture.

[0040] The content of the composite in the positive electrode active material layer is preferably 60% by mass to 97% by mass, more preferably 80% by mass to 96% by mass, and even more preferably 90% by mass to 95% by mass. By setting the content of the composite in the above range, it is possible to increase the discharge capacity per mass of the sulfur-based active material.

[0041] The positive electrode active material layer may contain a positive electrode active material other than the sulfur-based active material, but the content of the sulfur-based active material in the total positive electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, even more preferably 99 mass% or more, and particularly preferably 100 mass%.

[0042] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. The conductive agent does not include porous carbon constituting the composite. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them. It is also preferable to use carbon black (preferably acetylene black) in combination with CNT.

[0043] The content of the conductive agent (excluding the porous carbon in the composite) in the positive electrode active material layer is preferably 0.5% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 10% by mass or less. The upper limit of the content of the conductive agent in the positive electrode active material layer may be 5% by mass or 3% by mass. By setting the content of the conductive agent in the above range, the energy density per mass of the positive electrode can be increased.

[0044] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0045] The content of the binder in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, more preferably 2% by mass or more and 9% by mass or less. The upper limit of the content of the binder in the positive electrode active material layer may be 6% by mass or 4% by mass. By setting the content of the binder in the above range, the composite or the like can be stably maintained.

[0046] Examples of the dispersant include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the dispersant has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. The content of the dispersant in the positive electrode active material layer is preferably 0.05% by mass or more and 5% by mass or less, and more preferably 0.1% by mass or more and 2% by mass or less. The polysaccharide polymer may function as a thickener or a binder.

[0047] Examples of the thickener include polyacrylic acid (PAA). The content of the thickener in the positive electrode active material layer is preferably 0.05% by mass to 5% by mass, more preferably 0.1% by mass to 4% by mass. Polyacrylic acid may function as a binder.

[0048] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When the positive electrode active material layer contains a filler, the content of the filler in the positive electrode active material layer is preferably, for example, 0.1% by mass or more and 10% by mass or less. In one embodiment of the present invention, the positive electrode active material layer may not contain a filler.

[0049] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W, as components other than the composite, other positive electrode active materials, conductive agents, binders, dispersants, thickeners, and fillers.

[0050] The mass per unit area of ​​the positive electrode active material layer is not particularly limited, but is preferably 1 mg / cm 2 More than 30mg / cm 2 Less than 5 mg / cm is preferred. 2 More than 25mg / cm 2 Less than 10 mg / cm is more preferable. 2 More than 20mg / cm 2 The following is even more preferable: When the mass per unit area of ​​the positive electrode active material layer is within the above range, it is possible to increase the discharge capacity per mass of the sulfur-based active material, for example.

[0051] The porosity of the positive electrode active material layer is not particularly limited, but is preferably 15% to 50%, more preferably 20% to 40%, and even more preferably 25% to 35%. When the porosity of the positive electrode active material layer is in the above range, the discharge capacity per mass of the sulfur-based active material can be increased.

[0052] The "porosity (%)" of the positive electrode active material layer is calculated by the formula (1-V2 / V1) x 100, where V1 is the apparent volume (volume including voids) of the positive electrode active material layer and V2 is the sum of the actual volumes of the materials constituting the positive electrode active material layer. The sum V2 of the actual volumes of the materials constituting the positive electrode active material layer can be calculated from the content of each material in the positive electrode active material layer and the true density of each material.

[0053] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0054] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, and carbonaceous materials are used as the material of the negative electrode substrate. Among these, nickel or nickel alloys are preferred. Examples of the negative electrode substrate include foil, vapor deposition film, mesh, and porous materials, and foil is preferred from the viewpoint of cost. Therefore, nickel foil or nickel alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0055] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0056] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material layer includes optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary. The optional components such as a conductive agent, a binder, a thickener, and a filler can be selected from the materials exemplified for the positive electrode. The negative electrode active material layer does not need to include optional components such as a conductive agent, a binder, a thickener, and a filler.

[0057] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0058] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for a lithium ion secondary battery. Examples of the negative electrode active material include metallic lithium; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; and Li4Ti5O 12 , LiTiO 2、 Examples of the negative electrode active material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the case of a negative electrode active material that does not contain charge transport ions such as lithium ions, a material doped with lithium ions or the like can be used.

[0059] Metallic lithium is preferred as the negative electrode active material. Metallic lithium may be pure metallic lithium consisting essentially of lithium element, or may be a lithium alloy containing other metal elements. Examples of the lithium alloy include a lithium silver alloy, a lithium zinc alloy, a lithium calcium alloy, a lithium aluminum alloy, a lithium magnesium alloy, and a lithium indium alloy. The lithium alloy may contain a plurality of metal elements other than the lithium element.

[0060] The negative electrode active material layer may contain other negative electrode active materials than metallic lithium. However, the negative electrode active material layer is preferably a layer substantially composed of metallic lithium (pure metallic lithium or lithium alloy). The lower limit of the content of lithium element in the negative electrode active material layer is preferably 80 mass%, more preferably 90 mass%, and further preferably 99 mass% or more. The upper limit of the content of lithium element in the negative electrode active material layer may be 100 mass%. The content of lithium element in the negative electrode active material layer may be within a range that is a combination of any of the above-mentioned lower limits and the above-mentioned upper limit.

[0061] The negative electrode active material layer may be a non-porous layer (solid layer) or a porous layer, but is preferably a non-porous layer. The negative electrode active material layer may be a layer of metallic lithium. The negative electrode active material layer may be a layer made of metallic lithium foil (pure metallic lithium foil or lithium alloy foil). The average thickness of the negative electrode active material layer in a charged state is preferably 5 μm or more and 2,000 μm or less, more preferably 30 μm or more and 1,200 μm or less, and even more preferably 100 μm or more and 800 μm or less.

[0062] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0063] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500° C. in an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800° C. Examples of materials that have a mass loss of a predetermined amount or less include inorganic compounds. That is, the heat-resistant layer may be an inorganic particle layer containing inorganic particles and a binder. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As inorganic compounds, these substances may be used alone or in combination of two or more. Among these inorganic compounds, silicon oxide, aluminum oxide, and aluminosilicate are preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.

[0064] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0065] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0066] (Non-aqueous electrolyte) The nonaqueous electrolyte includes a nonaqueous solvent. As the nonaqueous electrolyte, a nonaqueous electrolyte solution including a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent is preferably used. In one embodiment of the present invention, the nonaqueous electrolyte storage element may be a nonaqueous electrolyte storage element.

[0067] The non-aqueous solvent contains at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates (hereinafter also referred to as "cyclic carbonate (A)"). When the non-aqueous solvent contains such a cyclic carbonate (A), it is possible to increase the energy density per mass, etc. The cyclic carbonate (A) may contain a fluorinated unsaturated cyclic carbonate that is a fluorinated cyclic carbonate and an unsaturated cyclic carbonate.

[0068] The fluorinated cyclic carbonate refers to a compound in which some or all of the hydrogen atoms of a cyclic carbonate are replaced with fluorine atoms. The cyclic carbonate refers to a carbonate having a ring structure containing a carbonate group (-OC(=O)-O-). The fluorinated cyclic carbonate is preferably a fluorinated saturated cyclic carbonate. The fluorinated saturated cyclic carbonate refers to a fluorinated cyclic carbonate that does not have a carbon-carbon double bond and a carbon-carbon triple bond in the molecule.

[0069] Examples of the fluorinated cyclic carbonate include fluorinated ethylene carbonate such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC), fluorinated propylene carbonate, fluorinated butylene carbonate, and fluorinated vinylene carbonate. Among these, fluorinated ethylene carbonate is preferred, and FEC is more preferred. The fluorinated cyclic carbonate can be used alone or in combination of two or more.

[0070] The lower limit of the content of the fluorinated cyclic carbonate in the non-aqueous solvent may be 0 vol%, preferably 30 vol%, more preferably 40 vol%, further preferably 50 vol%, and may be 60 vol%, 70 vol% or 80 vol%. The upper limit of the content of the fluorinated cyclic carbonate in the non-aqueous solvent may be 95 vol%, or may be 90 vol%, 80 vol%, 70 vol%, 60 vol% or 50 vol%. The content of the fluorinated cyclic carbonate in the non-aqueous solvent may be within a range that combines any of the above lower limits and any of the above upper limits (however, the upper limit is greater than the lower limit). When the non-aqueous solvent contains an unsaturated cyclic carbonate, the non-aqueous solvent may not contain a fluorinated cyclic carbonate.

[0071] The unsaturated cyclic carbonate refers to a cyclic carbonate having a carbon-carbon double bond or a carbon-carbon triple bond in the molecule. The unsaturated cyclic carbonate preferably has a carbon-carbon double bond in the molecule. The unsaturated cyclic carbonate may have a carbon-carbon double bond or a carbon-carbon triple bond in the ring structure or in a portion other than the ring structure, but preferably has the bond in the ring structure. The unsaturated cyclic carbonate may be fluorinated or may not be fluorinated, but preferably is not fluorinated.

[0072] Examples of the unsaturated cyclic carbonate include vinylene carbonate (VC), methyl vinylene carbonate, ethyl vinylene carbonate, propyl vinylene carbonate, butyl vinylene carbonate, dimethyl vinylene carbonate, diethyl vinylene carbonate, dipropyl vinylene carbonate, vinyl ethylene carbonate, etc., and VC is preferred. One or more of the unsaturated cyclic carbonates can be used.

[0073] The lower limit of the content of the unsaturated cyclic carbonate in the non-aqueous solvent may be 0 volume %, 5 volume %, 10 volume %, 20 volume %, or 30 volume %. The upper limit of the content of the unsaturated cyclic carbonate in the non-aqueous solvent may be 95 volume %, 90 volume %, 80 volume %, 60 volume %, 40 volume %, 20 volume %, or 10 volume %. The content of the unsaturated cyclic carbonate in the non-aqueous solvent may be within a range that combines any of the above-mentioned lower limits and any of the above-mentioned upper limits (however, the upper limit is greater than the lower limit). When the non-aqueous solvent contains a fluorinated cyclic carbonate, the non-aqueous solvent may not contain an unsaturated cyclic carbonate.

[0074] The content of the cyclic carbonate (A) in the non-aqueous solvent is more than 50% by volume. The lower limit of the content of the cyclic carbonate (A) in the non-aqueous solvent may be 55% by volume, 60% by volume, 65% by volume, or 70% by volume. The upper limit of the content of the cyclic carbonate (A) in the non-aqueous solvent may be 95% by volume, or 90% by volume, 85% by volume, 80% by volume, 75% by volume, or 70% by volume. The content of the cyclic carbonate (A) in the non-aqueous solvent may be within a range that combines any of the above-mentioned lower limits and any of the above-mentioned upper limits (however, the upper limit is greater than the lower limit). In the non-aqueous electrolyte storage element according to one embodiment of the present invention, since the content of the cyclic carbonate (A) in the non-aqueous solvent is more than 50% by volume, it is considered that a charge-discharge reaction occurs due to the solid-phase diffusion of charge transport ions through the above-mentioned coating in the positive electrode. In other words, when the content of the cyclic carbonate (A) in the non-aqueous solvent is more than 50% by volume, a good coating is sufficiently formed on the surface of the composite, and the energy density per mass of the non-aqueous electrolyte storage element can be increased.

[0075] The non-aqueous solvent contains a fluorinated ether represented by the following formula (1) (hereinafter, also referred to as "fluorinated ether (B)"). When the non-aqueous solvent contains such a fluorinated ether (B), the discharge capacity per mass of the sulfur-based active material can be increased. R 1 -OR2 (1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

[0076] R 1 Examples of R include methyl, ethyl, propyl, and 1-methylethyl groups in which some or all of the hydrogen atoms have been substituted with fluorine atoms. 1 The number of carbon atoms in R is preferably 2 or 3. 1 The number of fluorine atoms is preferably 2 or more and 6 or less, and more preferably 4 or more and 6 or less.

[0077] R 1 Examples of the group represented by the formula (I) include a 1,1,2,2-tetrafluoroethyl group and a 1,1,2,3,3,3-hexafluoropropyl group.

[0078] R 2 The group represented by the formula: is a methyl group or an ethyl group, and an ethyl group is preferable.

[0079] Examples of the fluorinated ether (B) include methyl-1,1,2,2-tetrafluoroethyl ether, ethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,3,3,3-hexafluoropropyl methyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, etc. The fluorinated ether (B) can be used alone or in combination of two or more.

[0080] The lower limit of the content of the fluorinated ether (B) in the non-aqueous solvent is preferably 10% by volume, and may be 15%, 20%, or 25% by volume. The content of the fluorinated ether (B) in the non-aqueous solvent is less than 50% by volume. The upper limit of the content of the fluorinated ether (B) in the non-aqueous solvent may be 45%, 40%, 35%, or 30% by volume. The content of the fluorinated ether (B) in the non-aqueous solvent may be within a range that combines any of the above-mentioned lower limits and any of the above-mentioned upper limits. When the content of the fluorinated ether in the non-aqueous solvent is within the above-mentioned range, the discharge capacity per mass of the sulfur-based active material of the non-aqueous electrolyte storage element can be increased.

[0081] The lower limit of the total content of the cyclic carbonate (A) and the fluorinated ether (B) in the non-aqueous solvent is preferably 80% by volume, more preferably 90% by volume, and may be 95% by volume or 98% by volume. The upper limit of the total content of the cyclic carbonate (A) and the fluorinated ether (B) in the non-aqueous solvent may be 100% by volume, and the non-aqueous solvent may be substantially composed of only the cyclic carbonate (A) and the fluorinated ether (B). When the non-aqueous solvent is substantially composed of only the cyclic carbonate (A) and the fluorinated ether (B), the effect of increasing the discharge capacity per mass of the sulfur-based active material can be particularly well achieved. The total content of the cyclic carbonate (A) and the fluorinated ether (B) in the non-aqueous solvent can be within a range that combines the above-mentioned lower limit and any of the above-mentioned upper limits.

[0082] The non-aqueous solvent may further contain other solvents than the cyclic carbonate (A) and the fluorinated ether (B). Examples of the other solvents include cyclic carbonates other than the cyclic carbonate (A), chain carbonates, ethers other than the fluorinated ether (B), esters, amides, nitriles, etc. Examples of the other cyclic carbonates include non-fluorinated saturated cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and chloroethylene carbonate. Examples of the chain carbonates include diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diphenyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, and bis(2,2,2-trifluoroethyl) carbonate.

[0083] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0084] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, LiPF6 and LiN(SO2F)2 are more preferred, and LiN(SO2F)2 is even more preferred. Also preferred are imide salts such as LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9), with LiN(SO2CF3)2 being more preferred.

[0085] The content of electrolyte salt in the non-aqueous electrolyte or non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolytic solution or the nonaqueous electrolyte can be increased.

[0086] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, and busulfan. Examples of the additives include sulfane, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, etc. These additives may be used alone or in combination of two or more.

[0087] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0088] The upper limit of the viscosity of the non-aqueous electrolyte or non-aqueous electrolyte at 25°C is preferably 6.5 mPa·s, more preferably 6.0 mPa·s, and may be 5.5 mPa·s, 5.0 mPa·s, 4.5 mPa·s, or 4.0 mPa·s. The lower limit of the viscosity may be 0.5 mPa·s, or may be 1.0 mPa·s, 1.2 mPa·s, 1.4 mPa·s, 1.6 mPa·s, 1.8 mPa·s, 2.0 mPa·s, 2.4 mPa·s, or 2.8 mPa·s. The viscosity may be within a range that combines any of the lower limits and any of the upper limits. The viscosity is measured using an Anton Paar LOVIS2000ME as a measuring device, and the ambient temperature of the room in which the measuring device is placed is set to 25°C.

[0089] The nonaqueous electrolyte may be a combination of a nonaqueous electrolyte solution and a solid electrolyte. The solid electrolyte may be selected from any material that has lithium ion conductivity and is solid at room temperature (for example, 15°C to 25°C). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halide solid electrolytes, and polymer solid electrolytes.

[0090] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0091] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0092] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.

[0093] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0094] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods, and includes, for example, preparing a positive electrode, preparing a negative electrode, preparing a separator, preparing a nonaqueous electrolyte, producing an electrode assembly using the positive electrode, the negative electrode, and the separator, and housing the electrode assembly and the nonaqueous electrolyte in a container.

[0095] The prepared positive electrode includes a composite of a sulfur-based active material and porous carbon. The specific form and preferred form of the prepared positive electrode are the same as the specific form and preferred form of the positive electrode included in the nonaqueous electrolyte storage element according to one embodiment of the present invention described above. Preparing the positive electrode may be preparing the positive electrode. The positive electrode can be prepared, for example, by applying a paste-like positive electrode mixture (positive electrode mixture paste) directly or via an intermediate layer to a positive electrode substrate, and drying the paste to form a positive electrode active material layer. The positive electrode mixture paste includes a composite of a sulfur-based active material and porous carbon, other components constituting the positive electrode active material layer, and a dispersion medium.

[0096] The preparation of the negative electrode may be the fabrication of the negative electrode. The specific form and preferred form of the prepared negative electrode are the same as the specific form and preferred form of the negative electrode included in the nonaqueous electrolyte storage element according to one embodiment of the present invention described above. The negative electrode having metallic lithium can be fabricated by laminating a negative electrode active material layer containing metallic lithium directly or via an intermediate layer on a negative electrode substrate, and pressing or the like. The negative electrode active material layer containing metallic lithium may be a pure metallic lithium foil or a lithium alloy foil. The fabrication of the negative electrode can also be performed in the same manner as the fabrication of the positive electrode.

[0097] The non-aqueous electrolyte to be prepared includes a non-aqueous solvent, the non-aqueous solvent includes a cyclic carbonate (A) and a fluorinated ether (B), and the content of the cyclic carbonate (A) in the non-aqueous solvent is more than 50% by volume. Specific and preferred forms of the non-aqueous electrolyte to be prepared are the same as those of the non-aqueous electrolyte included in the non-aqueous electrolyte storage element according to one embodiment of the present invention described above. Preparing the non-aqueous electrolyte may be preparing the non-aqueous electrolyte. The preparation of the non-aqueous electrolyte can be performed, for example, by mixing an electrolyte salt and a non-aqueous solvent.

[0098] The electrode assembly can be produced by stacking or winding a positive electrode and a negative electrode with a separator interposed therebetween.

[0099] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0100] The manufacturing method may include performing initial charging and discharging on an undischarged nonaqueous electrolyte storage element. The initial charging and discharging is usually started with discharging. The first discharge or the like may be called chemical conversion treatment. The number of times of charging and discharging in the initial charging and discharging is not particularly limited. Through the initial charging and discharging or chemical conversion treatment, a good coating is formed on the surface of the composite of the positive electrode by reacting a part of the positive electrode with the nonaqueous electrolyte.

[0101] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0102] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium-sulfur battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, capacitors, etc.

[0103] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0104] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0105] [Example 1] (Preparation of positive electrode) Elemental sulfur, which is a sulfur-based active material, and porous carbon ("CNovel" manufactured by Toyo Tanso Co., Ltd.) were mixed in a mass ratio of 70:30. This mixture was placed in a sealed electric furnace. After argon flow for 1 hour, the temperature was increased to 150°C at a rate of 5°C / min and held for 5 hours, and then allowed to cool to 80°C, the temperature at which elemental sulfur solidifies. Thereafter, the temperature was increased again to 300°C at a rate of 5°C / min and held for 2 hours for heat treatment to produce a composite (sulfur-porous carbon composite: SPC). A positive electrode mixture paste containing the composite obtained above, acetylene black and CNT as conductive agents, CMC as dispersant, PAA as thickener, and SBR as binder, was applied to an aluminum positive electrode substrate (average thickness 15 μm) using water as a dispersion medium, and then dried. Note that the mass per unit area of ​​the positive electrode active material layer after drying the dispersion medium was 15 mg / cm. 2 The amount of the positive electrode mixture paste applied was adjusted so that the positive electrode active material layer was laminated on the positive electrode substrate by the above steps. The porosity of the positive electrode active material layer in the obtained positive electrode was 30%.

[0106] (Preparation of the negative electrode) As the negative electrode, a pure metallic lithium foil (average thickness 600 μm) was prepared.

[0107] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) as a fluorinated cyclic carbonate, vinylene carbonate (VC) as an unsaturated cyclic carbonate, and ethyl-1,1,2,2-tetrafluoroethyl ether (ETFEE) as a fluorinated ether (B) were mixed in a volume ratio of 43:43:13 in a nonaqueous solvent, and LiN(SO2CF3)2 was added as an electrolyte salt at a concentration of 1.0 mol / dm 3The viscosity of the resulting non-aqueous electrolyte at 25°C was measured by the above-mentioned method and was found to be 4.1 mPa·s.

[0108] (Assembly of non-aqueous electrolyte storage element) The separator was prepared by laminating inorganic particle layers on both sides of a polyethylene microporous film. The positive electrode, negative electrode, separator and nonaqueous electrolyte were used to obtain a nonaqueous electrolyte storage element of Example 1.

[0109] [Examples 2 to 11, Comparative Examples 1 to 5] Nonaqueous electrolyte storage elements of Examples 2 to 11 and Comparative Examples 1 to 5 were obtained in the same manner as in Example 1, except that the compositions of the nonaqueous solvents were as shown in Table 1. The nonaqueous solvents used were as follows. Table 1 also shows the viscosity at 25° C. of the nonaqueous electrolyte in each nonaqueous electrolyte storage element. FEC: Fluoroethylene carbonate VC: Vinylene carbonate ETFEE: Ethyl 1,1,2,2-tetrafluoroethyl ether HFPEE: 1,1,2,3,3,3-Hexafluoropropyl ethyl ether TFETFPE: 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether

[0110] [evaluation] (Charge-discharge cycle test) Each of the obtained nonaqueous electrolyte storage elements was first subjected to constant current discharge at a current of 0.1 C down to 1.0 V as a chemical conversion treatment. Thereafter, constant current charging was performed at a current of 0.1 C up to 3.0 V. Next, constant current discharging was performed at a current of 0.1 C up to 1.0 V. Note that a 10-minute pause was provided after discharging and charging. Discharging, charging, and pausing were all performed in a thermostatic chamber at 25°C. The quantity of electricity per mass of the sulfur-based active material (sulfur alone) during the discharge after the above charging was calculated as the discharge capacity (discharge capacity per mass of the sulfur-based active material). The results are shown in Table 1.

[0111] [Table 1]

[0112] As shown in Table 1, the discharge capacity per mass of the sulfur-based active material of each nonaqueous electrolyte storage element of the embodiment was 1,190 mAh / g or more, and the discharge capacity per mass of the sulfur-based active material was large. In addition, for example, by comparing Comparative Example 1 with Examples 1 to 4 and 11, it was confirmed that the viscosity of the nonaqueous electrolyte was reduced by including fluorinated ether (B) in the nonaqueous electrolyte. On the other hand, in Comparative Examples 2 and 3 in which TFETFPE in which two fluorinated alkyl groups are bonded to an oxygen atom was included in the nonaqueous electrolyte, the viscosity of the nonaqueous electrolyte was reduced, but the discharge capacity per mass of the sulfur-based active material was not sufficiently increased. In addition to being able to reduce the viscosity of the nonaqueous electrolyte, the fluorinated ether (B) represented by the above formula (1) can improve the wettability of the nonaqueous electrolyte to the composite due to its molecular structure, and as a result, it is considered that the discharge capacity can be sufficiently increased. [Industrial Applicability]

[0113] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0114] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode including a composite of a sulfur-based active material and porous carbon, and Non-aqueous electrolyte containing non-aqueous solvent Equipped with The non-aqueous solvent is at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates; Fluorinated ethers and Including, The content of the cyclic carbonate in the non-aqueous solvent is more than 50% by volume, The fluorinated ether is represented by the following formula (1): R 1 -O-R 2 ・・・(1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the fluorinated ether in the nonaqueous solvent is 10% by volume or more and less than 50% by volume.

3. The nonaqueous electrolyte storage element according to claim 1 or 2, further comprising a negative electrode containing metallic lithium.

4. Providing a positive electrode comprising a composite of a sulfur-based active material and a porous carbon; and Providing a non-aqueous electrolyte including a non-aqueous solvent. Equipped with The non-aqueous solvent is at least one cyclic carbonate selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates; Fluorinated ethers and Including, The content of the cyclic carbonate in the non-aqueous solvent is more than 50% by volume, The method for producing a nonaqueous electrolyte storage element, wherein the fluorinated ether is represented by the following formula (1): R 1 -O-R 2 ・・・(1) (In formula (1), R 1 R is a fluorinated alkyl group having 1 to 3 carbon atoms. 2 is an alkyl group having 1 or 2 carbon atoms.

Citation Information

Patent Citations

  • Mesoporous carbon composite material and secondary battery using the same

    JP2010095390A